Cyberbullying: the mental health impact and strategies - Zakaria, Rozanizam (Revon Media Sdn Bhd, 2024)
The findings from the Adolescents Health Survey 2022 by the National Institute of Health and the Ministry of Health (MoH) have certainly alarmed us about the importance of cyberbullying issues among adolescents in Malaysia.